The Protective Effect of Betaine on Inhibition of Rifampin-Induced Liver Damage in Rats - P Peiravi; H Mohammadi; A Rashidiani-Rashidabadi; M Mohammadi; A Adineh (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2024)
Background and Objective: Rifampin is one of the antibiotic drugs that is usually used to treat tuberculosis and is considered a strong toxic agent for the liver. Therefore, this study was conducted to investigate the effects of betaine administration on rifampin-induced liver damage in rats. Methods: This experimental study was conducted on 60 male Wistar rats in 6 groups of 10. Liver damage and induction of oxidative stress were caused by oral administration of rifampin 100 mg/kg of body weight for 14 consecutive days. Different doses of betaine (10, 50 and 100 mg/kg of body weight) were administered by gavage to the sick rats. At the end of the treatment course, liver damage caused by rifampin was investigated by examining serum biochemical factors (ALT, AST, LDH, Bilirubin), and reactive oxygen species (ROS), glutathione (GSH), antioxidant capacity (FRAP), and lipid peroxidation (LPO), and histopathological changes in liver tissue were evaluated. Findings: Serum ALT level in the group that received rifampin (201±7821) was significantly higher than the control group (26±281) (p=0.0031). The serum level of AST in the group that only received rifampin (684±118) was significantly higher than the control group (50±1021) (AST=706). The amount of ROS was also significantly increased in the patient group (216,000±1001) compared to the control group (982,090±8332) (p=0.002). Also, the amount of LPO in the group that received rifampin (8.24±1.63) increased significantly compared to the control group (1.19±0.13) (p=0.021). Conclusion: The results of the study showed that betaine can reduce liver damage caused by rifampin and its consequences.